FIGURE 11 in Description of Oromurcia magadanensis sp. nov. (Acari, Oribatida, Ceratozetidae) from Russia, with remarks on biogeography of the genus Oromurcia Thor, 1930 - Ermilov, Sergey G.; Makarova, Olga L.; Behan-Pelletier, Valerie M. (Zenodo, 2022)
FIGURE 11. Collecting place of Oromurcia magadanensis sp. nov.: A—landscape of the Ola Plateau, Magadan Region, 60°39' N, 151°16' E; B—snowbed in the stream gully (the place of collection, 1023 m a.s.l., is indicated by an yellow arrow); C, D—rocky slope of a snowbed with vegetation patches dominated by Oxyria digyna and Artemisia kruhsiana (C) or Ranunculus pygmaeus and Sanionia uncinata (D). Published as part of Ermilov, Sergey G., Makarova, Olga L. & Behan-Pelletier, Valerie M., 2022, Description of Oromurcia magadanensis sp. nov. (Acari, Oribatida, Ceratozetidae) from Russia, with remarks on biogeography of the genus Oromurcia Thor, 1930, pp. 30-52 in Zootaxa 5187 (1) on page 44, DOI:10.11646/zootaxa.5187.1.5, http://zenodo.org/record/7078260